Phenomenology and Cognitive Neuroscience: Can a Process Ontology Help Resolve the Impasse?. Issue 2 (3rd April 2018) - Pain, Ross
Abstract: Shaun Gallagher [2019 ] argues for a 'non-classical' conception of nature, which includes subjects as irreducible constituents. As such, first-person phenomenology can be naturalised and at the same time resist reduction to the third-person. In the first part of this paper, I raise three concerns for the claim that nature is irreducibly subject-involving. In the second part of the paper, I suggest that embracing a process ontology could help strengthen Gallagher's proposal.